Hubungan Antara Stres Terhadap Guru Dengan Prokrastinasi Akademik Pada Siswa SMA Muhammadiyah 2 Yogyakarta - Sari, Dewi Novita (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
Abstract This research aims to know the relationship the stress on teachers with academic prokrastination in high student of Muhammadiyah 2 yogyakarta. Subjects in this study were 120 students of class XII IPA and IPS. This research using methods quantitative data by using a measuring instrument in form of psychological scale of the stress on teachers and scale academic procrastination. Technique the sample in research is using cluster random sampling and by lottery at random. The data of research in analyzed by used technique correlation product moment of pearson with used the aid program spss 16.0 for windows. The results of this study showed that there is a very significant positive relationship between stress on teachers with academic procrastination in high school students. This is shown by the correlation coefficient (r) positive 0,311 with p = 0,001 (p < 0,01). Categories of subjects showed that the stress level on the teachers included in the category are of 73,3 % and academic procrastination students are included in category are of 66,7 %. Effective contribution of stress on teachers with academic procrastination indicated by the coefficient of the determinant () = 9,7 % which means that there are 9,7 % of teacher stress can enhance the appearance of the academic procrastination while as many as 90,3 % are influenced by other factors not examined. Based on the research result, it can be concluded that there is very significant positive relationship between stress on teachers with students on academic procrastination. This suggests that the higher the stress on teachers then the higher academic procrastination conducted by students, instead the lower stress on teachers then the lower academic procrastination are done by the students.Key word : stress on teachers, academic procrastination